EXPERIENTIAL LEARNING IN LIBRARY AND INFORMATION SCIENCE (LIS) EDUCATION THROUGH OUT-CAMPUS PRACTICUM - Quijano, Grace D. (Journal of Philippine Librarianship, 2016)
This qualitative study explored the learning experiences of LIS students during the library out-campus practicum. It specifically determined the tasks performed by the students, the competencies improved and acquired by the students, and the influence of out-campus practicum on the students’ description of an ideal librarian, and on how they view their career in LIS five years after graduation. An unstructured questionnaire was used to gather data from 32 fourth year students of the Bachelor of Library and Information Science (BLIS). Journals of students as well as classroom discussions at the end of the practicum period also provided essential data. Responses were grouped into themes or categories based on thematic analysis. Results showed that out-campus practicum enabled students to experience a variety of LIS related tasks. Through this practicum, students improved their personal and professional competencies; they also acquired other personal competencies. Based on their experiences in the workplace, students described an ideal librarian primarily in terms of values/attitudes necessary in the field of LIS. After the out-campus experience, most students viewed themselves as successfully employed in different libraries and information centers five years after graduation.
Keywords: experiential learning, out-campus practicum, competencies